Jordan Triple Higher (Ïƒ,Ï„)-Homomorphisms on Prime Rings - Salih, Salah M.; Sulaiman, Neshtiman N. (Iraqi Journal of Science, 2020)
In this paper, the concept of Jordan triple higher -homomorphisms on primerings is introduced. A result of Herstein is extended on this concept from the ring into the prime ring . We prove that every Jordan triple higher -homomorphism of ring into prime ring is either triple higher -homomorphism or triple higher -anti-homomorphism of into .